Narrativa crítico-reflexiva sobre minhas vivências no curso de medicina da universidade federal de são carlos visão sobre o curso, a universidade e a cidade de são carlos na perspectiva de um homem preto - Silva, Guilherme dos Santos (Universidade Federal de São Carlos, 2024)
This work is a critical-reflexive narrative that explores the experience of a black student on the medical course at the Federal University of São Carlos. The author addresses challenges and personal experiences that involve insertion in a predominantly white and elite academic environment, contrasting moments of welcome with episodes of discrimination and violence, both experienced and observed. The narrative allows analysis these experiences through the theoretical perspective of relevant authors in the field of anti-racist resistance. Based on these experiences, the author reflects on the impact of these years of graduation in the construction of their identity and in their formation as future health professional. In conclusion, he highlights how this
Critical-reflective narrative about my experiences in the course of medicine of the federal university of são carlos vision about the course, the university and the city of são carlos from the perspective of a black man
Keywords: Narrativa; Graduação; Medicina; Homem; Preto; Narrative; Graduation; Medicine; Man; Black; CIENCIAS SOCIAIS APLICADAS